Editorial: Communication channels of research in political science and international relations - Miranda-Medina, Carlos (Política, Globalidad y Ciudadanía, 2019)
This editorial presents the communication channels that political science and international relations researchers have in the Scopus and Redalyc databases. This has been addressed from the theory of the analysis of the scientific domain, which consists in the study of the fields of knowledge (domains of knowledge) in direct connection with thought communities or discursive communities, based on the social division of work in society ( Hjorland & Albrechtsen, 1995). The scientific domain has as main characteristics the speech unit, the communication channels and the use of literature in a common way by the members of the community. In this case, the journals that are part of the communication channels through which researchers transmit and receive research advances in Political Science and International Relations will be analyzed. For this, the number of journals included in the databases that are linked to the subject area will be identified. Related to Scopus, it was decided to use the information registered by Scimago Rank, which uses Elsevier's information as input; on the other hand, the journals included in Redalyc were identified. In Scimago it was found that it is included in the area of social sciences and in the thematic category of political sciences and international relations. These are integrated by 463 journals worldwide, of which 405 are restricted and 58 have open Access; geographically, it is identified that in Latin America there are 16 journals of the subject matter, contributing 14 in open Access. Redalyc is a database with regional bias for Latin America, the categories are separated in the disciplines of politics and international relations. In politics 34 journals are included. It is identified that the countries that contribute with the most journals are Mexico, Colombia, Spain and Brazil. In international relations are 12 magazines, Mexico and Colombia contribute with more than 50% of them. This makes it possible to identify that researchers in political science and international relations have an amount that is close to 0.02% of journals in the thematic area of the universe of 24,702 journals that integrate the Scimago ranking globally. At a Latino-American level, the number of journals included in the disciplines of politics and international relations reach 0.03% of the universe of 1,314 included in Redalyc. The number of journals is smaller considering that political sciences and international relations have been present for a long time in the different countries where thematic researches are carried out. It is also an interdisciplinary connection science in the areas of exact sciences, social sciences (Islas, Vera, & Miranda-Medina, 2018), humanities and engineering (Núñez, Sánchez, Sotelo, Miranda-Medina, & Osorio, 2017; Miranda-Medina, 2018). For this reason, the number of researchers who develop studies on the subject matter is high, which leads to demand more spaces in order to share the findings. Even so, it is important to highlight that the trend of social science publications is concentrated in book publications, book chapters, proceedings of conference, among others. Taking into consideration the above presented, it can be seen that there is a need to strengthen and qualify journals that address the topics of political science and international relations in Latin America and globally, that promote the dissemination of research advances with perspectives from the glocal level (Brenner, 1998). Taking this need as a reference, the School of Political Science and International Relations, has decided to improve the editorial, scientific, stability, accessibility and visibility quality of Revista Política, Globalidad y Ciudadanía journal, thus providing a communication space where the scientist discourse is presented on the subject. Revista Política, Globalidad y Ciudadanía is presented as a scientific journal whose main objective is to disseminate research results articles, which contribute to strengthening the spectrum of scientific knowledge in political science and international relations. For this, the editorial process of the journal was restructured, all documents are submitted to arbitration processes under the double blind peer modality, the editorial criteria of international publications were included, its ethical policy was adjusted and editorial practices were improved, suggesting that the journal will be evaluated and indexed in the different databases that generate global impact.